Three-Dimensional Seismic Response Analysis of Zhubi Reef in the South China Sea. (5th August 2021) - Bao, Xin; Liu, Jingbo; Li, Shutao; Wang, Fei
Abstract : Reef islands are valuable terrestrial resources for ocean exploitation and utilization but face the serious threat of earthquake disasters. This study takes Zhubi Reef in the South China Sea as the research object and establishes a three-dimensional (3D) reef-seawater model to investigate the seismic response of Zhubi Reef. The 3D local topography and the effect of fluid-solid interaction are comprehensively considered. The artificial boundaries of fluid and solid domains are adopted to simulate the wave radiation and absorption of the semi-infinite seabed and the infinite seawater layer. The boundary substructure method is used to input the seismic waves into the numerical reef models. The results indicate that the seismic responses, including the peak values of the ground motions and the acceleration response spectra, are significantly amplified over Zhubi Reef. The acceleration response spectra on the reef flat shift closer towards the low-period direction compared with those of the seismic waves input from the subsea bedrock. In addition, the 3D topographic effect on the seismic response of Zhubi Reef is studied through a comparative analysis between two-dimensional (2D) and 3D reef models. The distribution laws of the peak response in the middle region of the reef flat calculated by the 2D and 3D models agree well with each other, and the differences are obvious in the edge areas where the local 3D topographies change drastically.